Christians, cultural interactions, and India's religious traditions - Brown, Judith M.; Frykenberg, Robert Eric; Low, Alaine M.; Brown, Judith M. (W.B. Eerdmans, 2002)
Christianity has long been one of India's religious traditions, but the extent to which the faith has influenced Indian society and culture has never been well documented. This important book is the first to do so. Here a group of historians, missiologists, and religion scholars examines the fascinating but little known history of missionary Christianity in India, showing how it has played a significant role in the development of modern India at every level.
Includes bibliographical references and index
Keywords: India -- Church history; Indien; Aufsatzsammlung; Geschichte; Mission; Kulturkontakt; Christentum